2024
DOI: 10.1038/s41598-024-59669-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key risk factors for acute compartment syndrome in tibial diaphysis fracture patients

Ming An,
Ruili Jia,
Limei Wu
et al.

Abstract: Acute compartment syndrome (ACS) is a severe orthopedic issue that, if left untreated, can result in lasting nerve and muscle damage or even necessitate amputation. The association between admission laboratory blood test indicators and the occurrence of ACS in patients with tibial diaphysis fractures is currently a subject of debate. The objective of this research was to identify the contributing factors for ACS in individuals suffering from tibial diaphysis fractures. In this retrospective study, we collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…More recently, in 2024, Ming et al [ 14 ] reviewed the risk factors for compartment syndrome with particular focus on laboratory based results. They found that male gender, crush injuries and elevated white cell count and LDH on admission bloods were predictive of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in 2024, Ming et al [ 14 ] reviewed the risk factors for compartment syndrome with particular focus on laboratory based results. They found that male gender, crush injuries and elevated white cell count and LDH on admission bloods were predictive of ACS.…”
Section: Discussionmentioning
confidence: 99%